Effects of Missing Data Patterns and Rates on the Accuracy of ARIMA Model for Electricity Consumption Forecasting - Bootwisas, Nassamon; Intarasat, Uparittha (Journal of Science Ladkrabang, 2026)
This study aims to investigate the effects of missing data patterns and missing rates on the forecasting accuracy of the ARIMA model from a methodological perspective using monthly electricity consumption data in Thailand from 2002 to 2025. A full factorial design was employed to simulate missing data under the Missing Completely at Random (MCAR) and Missing at Random (MAR) mechanisms at missing rates of 10%, 20%, and 30%, with 50 replications conducted for each experimental condition. Three widely used imputation methods in time series forecasting were applied, namely Last Observation Carried Forward (LOCF), Linear interpolation, and Kalman filtering. The results reveal that the imputation method is the most influential factor affecting forecasting accuracy, followed by the missing data rate. Kalman filtering consistently produced the lowest Root Mean Squared Error (RMSE) and demonstrated high stability across experimental conditions, whereas Linear interpolation consistently yielded the highest RMSE values. In addition, the performance of certain methods, particularly LOCF, varied substantially according to the proportion of missing data. These findings suggest that Kalman filtering is a robust and appropriate approach for handling incomplete energy time series data and can effectively support long-term energy consumption planning under data uncertainty.